Perbedaan Nilai Arus Puncak Ekspirasi antara Perempuan yang Memasak dengan Kayu Bakar dan LPG - Imaniar Hidayati Arindha; Ana Rima Setijadi; Novi Primadewi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: There are a lot of report about obstruction phenomenon because of firewoods use for fuel consumption of cooking. Its known from decrease value of PEF examination. Methods: This research was an analytical descriptive research using cross sectional approach and had been done in March 2012 in Giripeni Wates. The subjects were a woman who cooking use firewood and LPG. Data was collected by using purposive random sampling method. Data was analyzed using Chi Square test through SPSS 17.00 for Windows. Results: This research showed a mean of peak flow values in woman who cooking use firewood are 63,49 13,01 and LPG are 82,82 6,57. t-test shows p = 0,000 and Chi Square shows p = 0,003, Odd Ratio = 5,23. Conclusion: there were significant differences of PEF between a woman who cooking use firewood and LPG, firewood user has risk 5,23 bigger than LPG user. Keyword: Peak Ekspiratory Flow (PEF), firewood, LPG